Live migration using checkpoint and restore in userspace (CRIU): Usage analysis of network, memory and CPU - Adityas Widjajarto; Deden Witarsyah Jacob; Muharman Lubis (Institute of Advanced Engineering and Science, 2021)
Currently, cloud service providers have used a variety of operational mechanisms to support the company's business processes. Therefore, the services are stored on the company's server, which presents in the form of infrastructure, platform, software, and function. There are several vulnerabilities that have been faced in the implementation such as system failure, natural disasters, human errors, or attacks from unauthorized parties. In addition, the time of unavailability of services can be minimized by doing an LM, in which many servers have been used the containers to behave like a service provider. Actually, its existence replaces the virtual machine that requires more resources although the process only can be done through docker with checkpoint and restore in userspace (CRIU). In this research, LM processes are done to the docker container using CRIU by analyzing the quality of service (QoS), memory, and CPU usage. Thus, the simulation is carried out by establishing the LM using 2 (two) different platforms through scenarios with one and three containers respectively. The performance analysis results aim to examine several indicators in comparison with the achievable result to reduce problems that occurred in the cloud service.